Analysis of the frequencies and functions of CD4+CD25+CD127low/neg, CD4+HLA-G+, and CD8+HLA-G+ regulatory T cells in pre-eclampsia. (June 2019) - Zare, Maryam; Namavar Jahromi, Bahia; Gharesi-Fard, Behrouz
Highlights: CD4 + CD25 + CD127 low/neg and CD8 + HLA-G + Treg cells significantly diminished in preeclamptic women. There was a shift toward the lower suppressive capacity of CD4 + CD25 + CD127 low/neg and CD4 + HLA-G + Treg cells in preeclamptic patients. Impaired immune tolerance might be clinically important in the context of pre-eclampsia. CD4 + HLA-G + and CD8 + HLA-G + Treg cells were significantly higher in pregnant subjects compared to non-pregnant women. HLA-G + regulatory T cell subsets might be important players in pregnancy. Abstract: Most of the investigations on regulatory T cells (Treg) have focused on CD4 + CD25 + Foxp3 + Treg cells. Although new subsets of these cells such as CD4 + CD25 + CD127 low/neg, CD4 + HLA-G +, and CD8 + HLA-G + Treg cells have been introduced, documents regarding these populations are limited or controversial in case of pregnancy and pre-eclampsia (PE). Here, we investigated the frequencies of the three aforementioned Treg cell subsets in the peripheral blood of non-pregnant (n = 15), healthy pregnant, and preeclamptic women (n = 17 in each group) using flow cytometry. We also assessed the ability of the isolated CD4 + CD25 + CD127 low/neg and CD4 + HLA-G + Treg cells to suppress responder T cells proliferation and cytokine secretion using CFSE dye dilution and ELISA technique. Our results showed that the frequency of CD4 + CD25 + CD127 low/neg Treg cells was significantly lower in preeclamptic women ( p = 0.001). Also, this subset negatively correlated with both systolic (R= - 0.401, p = 0.004) and diastolic (R= - 0.541, p = 0.001) blood pressures. Regarding CD4 + HLA-G + and CD8 + HLA-G + Treg cells, the mean percentages of these cells were significantly higher in the context of normal pregnancy ( p < 0.01). Finally, our results in the functional assay experiments did not show statistically significant differences between groups ( p ≥ 0.05), but they reveal a shift toward the lower suppressive capacity of CD4 + CD25 + CD127 low/neg and CD4 + HLA-G + Treg cells in preeclamptic patients which might be clinically important. In conclusion, a significant decrease in the frequency of Treg cell subsets and also a shift toward the lower suppressive capacity of these cells in preeclamptic patients may lead to immunological maladaptation in the context of PE.